2011
DOI: 10.1017/s1041610211000238
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset-psychosis: cognition

Abstract: The present results suggest cognitive deficits (mostly of executive functions) and vascular and neurodegenerative vulnerability in LOPS. Further studies with larger samples are needed to confirm the present findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 54 publications
(51 reference statements)
0
17
0
Order By: Relevance
“…The detailed method and cognitive results were presented in a previous report [39]. In summary, although VLOSLP and EOS patients did not meet the diagnostic criteria for dementia at onset of the psychotic disorder, the results showed that the groups presented at follow-up with cognitive deficits in several domains, and 20% of VLOSLP had developed dementia overtime (after onset of psychotic disorders) compared to 5.9% of EOS [39].…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…The detailed method and cognitive results were presented in a previous report [39]. In summary, although VLOSLP and EOS patients did not meet the diagnostic criteria for dementia at onset of the psychotic disorder, the results showed that the groups presented at follow-up with cognitive deficits in several domains, and 20% of VLOSLP had developed dementia overtime (after onset of psychotic disorders) compared to 5.9% of EOS [39].…”
Section: Introductionmentioning
confidence: 76%
“…Both groups presented with vascular risk factors, and 69% of the VLOSLP for whom neuroimaging data were available at follow-up presented abnormalities, mostly vascular. Only 6/17 EOS had CT-scans and abnormal findings were reported in 33% of these patients (see Girard et al [39], for further details and dosages of medications). Few active symptoms of depression and/or anxiety were present in a small number of patients at the current evaluation (follow-up) whereas most patients suffered from significant anxious and depressive symptoms in the past.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations